Comparison of mechanical properties of polyester composites reinforced with autochthonous natural fibres: flax and hemp - Rocha, João (2017)
Natural fibre composites have some mechanical and environmental advantages when compared with synthetic ones and the environmental advantage can, even, be improved if the base materials are autochthonous. In this work are analysed two factors concerning natural fibre composites characteristics: fibre type influence and fibre surface alkali-silane treatment. For this purpose, it was defined an orthogonal array of experiments where the levels of sodium hydroxide (NaOH) concentration were changed and used over flax and hemp fibres. The matrix of composite was, always, polyester resin and six plates were manufactured with different combinations among alkali-silane treatment and fibre types. To evaluate the composite mechanical characteristics eighteen tensile tests were performed and it was calculated the average tensile strength for each combination. The combination that brings the highest value of tensile strength was the flax composite associated with the alkali-silane fibre surface treatment with 5% of concentration of NaOH, which resulted in 113 MPa. The most influent factor to maximize the tensile strength was the alkali-silane fibre surface treatment, with a contribution of 53.0%.